Mobile forms vs the total content of thallium in activated sludge - Bożena Karbowska; Włodzimierz Zembrzuski; Joanna Zembrzuska (Archives of Environmental Protection, 2022)
Sewage sludge from municipal wastewater treatment plants is currently a serious environmental problem, given its diversity due to the variability of time and heavy metal content. Current research on the monitoring of heavy metals is based on the determination of Pb, Cd, Hg, Ni, Zn, Cu and Cr. This makes any thallium content data difficult to access. The study estimated the degree of contamination of sewage sludge with thallium. The sludge samples came from a sewage treatment plant located in Poland. The results are presented for the total concentration of thallium and its mobile forms. These samples were analyzed by differential pulse voltammetry. The results showed that the average thallium content was 0.203 μg/g and its mobile form was 0.025 μg/g. The conducted research shows that almost 13% of thallium from sewage sludge can be gradually released into the environment.